BIROKRASI PELAYANAN KESEHATAN PADA PASIEN YANG MENGGUNAKAN KARTU BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KESEHATAN DI RUMAH SAKIT UMUM DAERAH (RSUD) ARIFIN ACHMAD PROVINSI RIAU - Melisa, Ivo; Bahri, Syamsul (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Organizing Board Healt Social Safety is a social security program which is a policy of the government to give the warranty over the need for basic needs for Indonesian people. The district general hospital is a one of hospital that receive the reference from the government to give health services for the Organizing Board Healt Social Safety users, but the services provided are often complained of by patients, the process is complicated and takes a long time. Therefore it is necessary to study the problem of bureaucracy of health services in the Regional General Hospital (RSUD) Arifin Achmad Pekanbaru with the formulation of the problem namely: How the bureaucracy of health services carried out and the factors that influence the health service bureaucracy. This research is done in Arifin Achmad the District General Hospital Pekanbaru. The purpose of this research is to know the health services bureucracy, an the factors that determine the healt services bureucracy over the patients in Arifin Achmad hospital. This research is using quaitative method by using accidental sampling technique based determined criteria. This research is done in 7 (seven) peoples that is administration staffs, doctors,Â and patients. The result of this research is that healty services bureucracy in Arifin Achmad hospital is still not good, because the services not balance. The solution is the hospital shoul improve the services quality towards yhe patients especially to the Organizing Board Healt Social Safety users.Â Â Keywords : Bureucracy, Organizing Board Healt Social Safety